Inventários Beck para crianças e adolescentes: revisão sistemática da literatura - Morais, Résia Silva de (2014)
The cognitive theory / therapy (CT) produced profound changes in psychiatry and psychology contributing thus to treat a variety of disorders. In diagnostic terms, the CT use psychometric scales and other instruments. For example, in 1961, Beck developed the Beck Depression Inventory (BDI) revised in 1978 (BDI-1A) and in 1996 the BDI-II was published. In 2001, the Beck Youth Inventory (BYI-II) was prepared for children and adolescents aged 7-18 years consisting of an inventory of five scales that assess symptoms of depression, anxiety, anger, disruptive behavior and self-concept. The aim of this work was to construct a systematic review of national and international scientific production of the Beck Depression Inventory for Youth (BDI-Y), the Beck Anxiety Inventory for Youth (BAI-Y) and the Beck Disruptive Behavior Inventory for Youth (BDBI-Y); furthermore, we considered studies that employ these tools in the clinical area and overall health. The review was carried from the use of descriptors: Beck Depression Inventory for Youth , Beck Anxiety Inventory for Youth and Beck Disruptive Behavior Inventory for Youth . The references selection criteria were: presence of the descriptor in the text, articles written in English, Spanish and Portuguese; repeated references in other databases will be selected only in one base; references that were related to the theme, with the guiding criterion focus on using the BAI-Y , the BDI-Y and BDBI-Y. The results were: following criteria for inclusion, 11 articles, with the descriptor \"Beck Depression Inventory for Youth\"; with the descriptor \"Beck Anxiety Inventory for Youth\", 11 studies were selected. Already with the descriptor \"Beck Disruptive Behavior Inventory for Youth\" were selected only three references. Therefore, undertake a review of the scientific production of three inventories Beck Youth Inventory (BYI-II) was essential to verify the scarcity of studies about BDI-Y, BAI-Y and BDBI-Y. Results show no Brazilian studies, most are from the United States and only one reference reported use of Beck Inventories, second edition, adapted and validated for the Chinese reality. These results can contribute to raising awareness about the need to researchers to continue this discussion, considering the great necessity of their inclusion in research and research development with emphasis on studies of the psychometric properties of these instruments and their appropriateness to the Brazilian reality. Finally, with the guarantee of further studies, will be possible to evaluate the competence of this scales and their utility in the academic and clinical community.